Understanding and simplifying inversion recovery - Collins, Christopher (International Journal of Innovative Research in Medical Science, 2018)
The usage of magnetic resonance imaging (MRI) as a vital diagnosing tool has increased greatly since its beginnings in the late 1970’s and early 1980’s. One of the key features of MRI is its ability to create differing contrasts between tissues without the reliance on contrast enhancement drugs. Some atomic nuclei are capable of absorbing and emitting radio-frequency (RF) when placed in an external magnetic field, the most common atoms utilised in MRI are hydrogen (specifically the hydrogen proton), this being due to their high abundance in the body, especially in water and fat. By using RF waves to excite nuclear spin transition and magnetic gradients within the scanner to localise signal, it is possible to pick up signal from tissues, in essence MRI maps the location of tissues containing hydrogen. The properties (T1 relaxation/T2 decay) of the hydrogen protons differ depending on the tissue, which can be exploited by MRI to create contrast, this is further utilised in the inversion recovery (IR) pulse sequence. IR allows the radiographer to suppress signal from certain tissues which can enhance the contrast of the image and help differentiate between certain pathologies. In conclusion understanding how IR works allows the radiographer to alter scan parameters to enhance images and show certain pathology which would normally be impossible to show.